Effectiveness of Field Visit in Community Medicine: A Randomized Control Trial - Rawal, Shridhar V (National Journal of Community Medicine, 2019)
Background: The community medicine is a major subject in un- dergraduate curriculum in India. Though much is said about methods and technologies to improve teaching in the subject, the scientific proof of field visits being better than class room teaching for understanding concepts like primary health care lacks. A ran- domized controlled trial, can give better idea of effectiveness of the intervention i.e. actual field visit to the heart of primary health care services-primary health center. Method: Double- blind block randomization trial with two arm parallel design. The intervention group and control group were subjected to a semi-structured questionnaire following interven- tion. Logistic regression for Odds ratio adjusted for sex and at- tendance calculated. Results: Crude and adjusted odds ratio highly significant in fa- vour of intervention group. However, on sub component analysis for adjusted odds ratio for both variables, data management at PHC was having odds ratio <1. Adjusted odds were significantly high, specially for functions of medical officer and staffing pattern of PHC. Conclusion: The randomization clearly suggests that field visit of primary health center helps students understand and realize con- cepts of primary health care better than classroom teaching. Repli- cation of such studies with larger sample size may help.